2022
DOI: 10.3390/antiox11101849
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Antibacterial Properties of an Achillea millefolium L. Extract and Its Fractions Obtained by Supercritical Anti-Solvent Fractionation against Helicobacter pylori

Abstract: The main objective of this work is to evaluate the potential utility of an Achillea millefolium extract (yarrow extract, YE) in the control of H. pylori infection. The supercritical anti-solvent fractionation (SAF) process of YE allowed the obtaining of two different fractions: yarrow’s precipitated fraction (YPF), enriched in most polar phenolic compounds (luteolin-7-O-glucoside, luteolin, and 3,5-dicaffeoylquinic acid), and yarrow’s separator fraction (YSF), enriched in monoterpenes and sesquiterpenes, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…[ 33 , 34 ] has been published to date. Most of the published research has investigated the anti-inflammatory activity of the polar extracts from Achillea spp., especially extracts from A. millefolium , using in vivo techniques [ 35 , 36 ]. This is the first report on the anti-inflammatory activity of the essential oil of A. grandifolia .…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 , 34 ] has been published to date. Most of the published research has investigated the anti-inflammatory activity of the polar extracts from Achillea spp., especially extracts from A. millefolium , using in vivo techniques [ 35 , 36 ]. This is the first report on the anti-inflammatory activity of the essential oil of A. grandifolia .…”
Section: Resultsmentioning
confidence: 99%
“…Yarrow ( Achillea millefolium L.), ribwort ( Plantago lanceolata L.), and sorrel ( Rumex acetosella L.) are among the best‐known plant species with different pharmaceutical uses. Yarrow contains polyphenols, mainly luteolin, monoterpenes, and sesquiterpenes (Villalva et al, 2022), and its extracts showed antimicrobial effects on pathogenic bacteria, including Salmonella (Karamenderes et al, 2002; Stojanović et al, 2005). Yarrow, as herb or oil, is listed in Substances Added to Food as flavoring agent or adjuvant by US Food and Drug Administration (FDA, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Achillea millefolium was also used in herbal tea mixes and phytopharmaceuticals. Previous studies revealed that Achillea millefolium extract has anticancer, antibacterial, anti-inflammatory, and antioxidant activities [ 4 ]. Saffron is one of the most valuable flowers produced in the Middle East.…”
Section: Introductionmentioning
confidence: 99%